Preliminary study on the medical image collections of the University of the Philippines College of Medicine - Camacho, Albert Allan N.; Quiros, Edgardo B. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2002)
Medical images are a vital information resource in the field of medicine. Its primary use is in educational, clinical and research reference. The University of the Philippines College of Medicine (UPCM) generates a great amount of this resource. How can these be managed in order to provide optimal acquisition, storage, and retrieval?
The different departments of the UPCM each have their own collections of medical images that practitioners hope to be made accessible in an interoperable environment within the local network by means of digitization. This study aimed to find out how many images the departments currently have, the manner of storage and collection, and make recommendations on how to properly manage the images in the context of a Picture Archiving and Communication System (PACS).Most of the images currently stored by the departments of UPCM are in analog format. Digitization efforts are is still in the initial stage. Only 13 percent (approximately 1500 images) of the collections of the responding departments are already in digital format. There was also a lack of image archiving standards and policies.
Recommendations were made on the conceptualization of a centralized PACS for the UPCM. Key considerations for image selection, archival policy, digitization, organization and image retrieval were identified.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines College of Medicine; Imaging systems in medicine; Image processing -- Digital techniques